MORPHOMETRIC AND APOPTOTIC STUDIES IN RAT PC-12 (PHEOCHROMOCYTOMA) CELLS EXPOSED TO NEUROTOXIC SHOCK - DEEPTI DUA; NUPUR S. SRIVASTAVA (International Journal of Pharma and Bio Sciences, 2016)
We investigated the effects of a potent antioxidant, lycopene, on the free radical-scavenging activity as evaluated by DPPH assay, FRAP assay, lipid peroxidation, nitric oxide and lipofuscin formation in rat PC- 12 cells exposed to neurotoxic shock by 6-Hydroxydopamine (6-OHDA). Cell viability was also determined using MTT assay in these samples. Cell morphology was studied using TUNEL assay prior and after treatment of cells with 6-OHDA and lycopene. In addition, we also determined the apoptotic characteristics prior and after treatment of cells with 6-OHDA and lycopene using flow cytometer. Lipid peroxidation levels were increased in PC-12 cells after treatment with 6-OHDA. Total antioxidant levels were found to be increased in cells treated with 6-OHDA and lycopene as compared to cells treated with 6-OHDA alone. But on further treatment of cells exposed to 6-OHDA with lycopene, the levels of these enzymes and the cell counts were increased to nearly 80% as compared to the control and lipid peroxidation levels were decreased to 75% as compared to the control. Altered activities of these antioxidant enzymes upon treatment with 6-OHDA were restored to almost normal level upon treatment of cells with lycopene. This may be due to the antioxidant property of lycopene. Lycopene exerted decreased lipofuscin content in cells treated with it. Lycopene significantly inhibited nitrite production by about 61% in cells exposed to neurotoxic shock. Our study demonstrated a protective effect of lycopene in rat PC-12 cells exposed to neurotoxic shock. Lycopene, through its antioxidant property, mediates free radical-scavenging activity and inhibits apoptosis.